An analysis of agricultural production efficiency of Yellow River Basin based on a three-stage DEA Malmquist model - Xiejun Cheng; Jinxin Bian; Dongmei He; Decai Tang (Humanities & Social Sciences Communications)
Abstract Agriculture functions as the cornerstone of national development, and the Yellow River Basin (YRB) plays a crucial role in China’s economy. This study examines agricultural production efficiency (APE) across nine YRB provinces from 2000–2022 by integrating static and dynamic analyses through the Data Envelopment Analysis (DEA) model and the Malmquist productivity index. By contrasting a three-stage DEA-Malmquist model that incorporates random managerial inefficiency with one that excludes it, we identify technological progress as the key driver of APE growth in the YRB, though with marked regional disparities. The study further systematically investigates determinants influencing APE, including environmental factors, and proposes evidence-based strategies to optimize agricultural productivity in the region. The findings highlight technological advancement as the dominant force behind total factor productivity growth, while environmental variables exert substantial influence on APE outcomes. Recommendations include promoting targeted efficiency improvements, fostering technological innovation, optimizing resource allocation, and strengthening policy coordination to achieve sustainable and efficient agricultural development in the YRB.